Aryl Annulation: A Powerful Simplifying Retrosynthetic Disconnection - Gillard, Rachel M.; Zhang, Jiajun; Steel, Richard; Wang, Jocelyn; Strull, Jessica L.; Cai, Bin; Chakraborty, Nilanjana; Boger, Dale L. (Synthesis, 2022)
Retrosynthetic deconstruction of a core aromatic ring is an especially simplifying retrosynthetic step, reducing the complexity of the precursor synthetic target. Moreover, when implemented to provide a penultimate intermediate, it enables late-stage divergent aryl introductions, permitting deep-seated core aryl modifications ordinarily accessible only by independent synthesis. Herein, we highlight the use of a ketone carbonyl group as the functionality to direct such late-stage divergent aryl introductions onto a penultimate intermediate with a projected application in the total synthesis of vinblastine and its presently inaccessible analogues containing indole replacements. Although the studies highlight this presently unconventional strategy with an especially challenging target in mind, the increase in molecular complexity (intricacy) established by the synthetic implementation of the powerful retrosynthetic disconnection, the use of a ketone as the precursor enabling functionality, and with adoption of either conventional or new wave (hetero)aromatic annulations combine to define a general and powerful strategy suited for widespread implementation with near limitless scope in target diversification.
Keywords: alkaloids; annulations; arenes; cycloaddition; heterocycles; vinblastine; late-stage modification; retrosynthetic disconnection; natural products